Regulated expression of follicle stimulating hormone receptor type III in cancer causing mouse ovarian surface epithelial cells - Zimmerman, Shawn (Kansas State University, 2007)
Follicle stimulating hormone (FSH) is known as the key hormone capable of causing proliferation of granulosa cells in the ovary. The classical receptor belongs to the G protein-coupled superfamily and is designated FSHR-1. A variant in the FSH receptor has been shown to be functional in mouse ovaries. The variant receptor is designated as FSHR-3, and when bound by FSH activates a pathway that shares similar characteristics to the growth factor type I receptor pathway, with no increase in cAMP. The FSHR-3 variant activates MAPK upon binding to FSH, and causes proliferation of cells on which it is known to be expressed. For example ID8 mouse ovarian surface epithelium cells (MOSEC), a cell line that when introduced in immunocompetent mice causes tumors similar to human ovarian cancer and which also express FSHR-3, proliferated in response to FSH. The present study explored the potential for decreasing expression of FSHR-3 protein. The RNA interference (RNAi) technique was used to insert small inhibitory RNA(siRNA) segments corresponding specifically to the R3 variant of the FSH receptor in ID8 MOSEC. Transfected cells were lysed and FSHR-3 protein was visualized using SDS Page and Western blotting analysis. A reduction in expression of FSHR-3 was observed in two of the transfection groups, with the greatest down-regulation of FSHR-3 being 30.1%. From these preliminary results we conclude that the FSHR-3 is expressed on ID8 cells, and that siRNA may be useful to reduce its expression. Thus, it may be possible to slow the growth of FSH-responsive tumors using siRNA to target the FSHR-3 receptor.
Keywords: Follicle Stimulating Hormone Receptor III; Mouse Ovarian Surface Epithelium Cells; Agriculture, Animal Pathology (0476); Biology, Animal Physiology (0433); Health Sciences, Oncology (0992)